IMPACT OF ORGANIZATIONAL COMMITMENT AND WORK SATISFACTION ON TURNOVER INTENTION - Mulyanto, Agus Iwan (Perspektif : Jurnal Ilmu Administrasi, 2019)
This study was conducted to investigate the impact of organizational commitment and job satisfaction to turnover intention felt by the operator employees’ one of Garment Company in Tangerang Selatan. Data were collected through survey and bibliography study. The 150 questionnaires have send to respondents and 147 were returned yielding response rate 98%. From the correlation and regression analysis, the study found that the correlation and the impact of turnover intention has supported.  From four hypotheses that have tested in this study, all hypotheses were supported. The result showed that organizational commitment and job satisfaction were negatively and significantly related to turnover intention and having negative influence on it.